Upaya Peningkatan Mutu Perilaku Kesehatan Reproduksi Anak Jalanan Perempuan di Kota Malang melalui Pendekatan Teori Keperawatan Johnson Behavior Sistem Model - Nurul Aini (Journal of Ners and Midwifery, 2014)
Adolescence is the age of the solid changes. At this time of great confusion adolescents experience in reaching his true identity. This period was characterized by growth, change, the emergence of a variety of occasions, and often face reproductive health risks. Sexual activity places adolescents at risk of challenges to various reproductive health problems. One part of the youth are a group of teenagers who are in a community of street children. The hard life on the streets with the unfavorable situation in which street children have to survive, forcing them to become adults before their time. Although they are socially categorized as a child, but almost all of them to adopt forms of behavior as a sign of rebellion against the maturity of some of the expectations that have been defined and determined by the local community. By adopting the mature form of behavior, they do not deserve the actions that should be done to children their age, which includes pre-marital sex (free sex), sexually transmitted diseases (STDs), use of drugs, homosexuality, and violence sexual. Easily they can acquire knowledge about sex influence attitudes toward sexual behavior of street children (Nurharjadmo, 1999). The low awareness and lack of knowledge of street children is likely to be one cause. Necessary handling and kepeduliaan of all parties to help alleviate them from such circumstances. Development of street children, especially in reproductive health issues for this still largely done by volunteers who are not health perpendidikan. Thus the involvement of the nursing profession as nursing care providers considered very important. This is consistent with the role of the nurse as educator, facilitator, coordinator, health reformers and observers (the National Workshop on Nursing 1983). This study aims to analyze the influence of coaching to nursing approach to the theory of "System Model Behavior" of the quality of reproductive health behavior of female street children. Research using experimental designs with pre-draft "Pre and Post Test Design. The population in this study were all female street children in Malang with a sample of respondents who take part in reproductive health coaching. Data is collected with the questionnaire enclosed. The results of the research done in getting the data that the quality of reproductive health behavior of female street children before treatment is given the majority (80%) have good manners, the remainder (20%), including less well with the average value of 17.76. Whereas after given treatment to be better with an average increase in value to 20.68. The details are as many as 76% in both categories and 24% is very good. Wilcoxon match pair test results to explain the value Asymp.Sig test (2-tailed) or p-value <Î±, namely (0.000 <0.05), so it can be concluded that the act of coaching to nursing approach to the theory of Johnson Behavior Model System can increase the mean average quality of reproductive health behavior of female street children inÂ  Malang.